Synchronous reinforcement device and method for laser compound plasma electrolytic polishing under total reflection condition
Patent Information
- Application Number
- CN202311782711.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-22
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2043-12-22
AI Technical Summary
目前存在的解决方案是在管状阴极内壁涂覆镜面涂层,但由于高能量密度激光直接辐照,因此镜面涂层会逐渐被破坏,具有较差的时效性
[0028]1.激光在管状阴极内通过全反射传输,其能量损耗要低于传统的镜面反射。同时全反射的光疏介质是超疏水涂层与电极液中的空气膜,激光不会直接作用于超疏水涂层上,因此具有较长的使用寿命。
Smart Images

Figure CN117983953B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a laser composite plasma electrolytic polishing synchronous strengthening device and method based on total internal reflection conditions, belonging to the field of laser composite plasma electrochemical processing. Background Technology
[0002] Additive manufacturing technology enables rapid, moldless forming of dense metal parts with complex structures. It is particularly suitable for the short-cycle, low-cost manufacturing of high-performance, difficult-to-machine, large, complex, and critical structural components such as titanium alloys and high-temperature alloys in critical equipment, and has become one of the cutting-edge research hotspots in the interdisciplinary field of international materials processing engineering and advanced manufacturing technology. However, current additive manufacturing of complex structural metal parts still has shortcomings in surface quality, forming accuracy, and overall performance, requiring polishing to meet their high service requirements. Polishing is a crucial process for ensuring the performance of additively manufactured metal parts and is of paramount importance for expanding the practical application of additively manufactured metal parts.
[0003] Plasma electrolytic polishing (PEP), which utilizes the principle of liquid-phase plasma electrolysis to polish metal surfaces, has gained widespread attention due to its advantages such as high efficiency, uniformity, minimal material damage, and environmental friendliness. This technology uses the high energy and localized gas explosions of plasma discharge to remove protrusions and oxide layers from the material surface, achieving a polishing effect. However, with the rapid expansion of additive manufacturing technology, further improving the overall surface performance of materials, beyond simply reducing the surface roughness of additively manufactured components, has become an important development trend for expanding the application fields of additive manufacturing. Plasma electrolytic oxidation (PEO), as an important technology for efficient surface treatment of complex additively manufactured parts, mainly improves the overall surface performance of additively manufactured metal components by breaking down the oxide layer on the metal surface and growing a reinforcing coating mainly composed of base metal oxides in situ. However, due to the inherent defects and high roughness of the original surface of additively manufactured metal components, PEO is currently usually used as a post-processing step for polished additively manufactured metal parts, which inevitably leads to additional manufacturing steps and costs.
[0004] From the perspective of process characteristics and discharge properties, the essential difference between plasma electropolishing and plasma electrooxidation lies only in the formation process of the dielectric barrier layer and the type of plasma discharge. Plasma electropolishing generates plasma by breaking down the gas film barrier layer, utilizing the high energy and local gas explosion of the plasma discharge to achieve the polishing effect. Plasma electrooxidation, on the other hand, utilizes the plasma discharge generated by the breakdown of the oxide layer, leveraging the instantaneous high temperature and high pressure environment and the rapid cooling effect of the electrolyte to promote the growth of the oxide film on the anode surface. Although plasma electropolishing and oxidation have significant differences in processing effects, theoretically, it is entirely feasible to achieve simultaneous processing of both by changing the formation of the dielectric barrier layer and the type of plasma discharge. However, there are few reports on the combined research of plasma electropolishing and plasma electrooxidation. Therefore, this invention proposes a method for simultaneous strengthening of plasma electropolishing, simultaneously preparing a strengthening coating on the polished surface.
[0005] The simultaneous enhancement of plasma electropolishing can be achieved through liquid-guided laser-jet electrochemical processing technology. However, in this technology, a large electric field is required between the cathode nozzle and the anode substrate to maintain the electrochemical reaction, resulting in a typically small distance between the anode and cathode. Most of the laser transmission occurs within the tubular cathode, leading to significant absorption of the laser energy by the inner wall. Current solutions involve coating the inner wall of the tubular cathode with a mirror coating, but this coating gradually deteriorates due to direct irradiation by high-energy-density lasers, exhibiting poor long-term effectiveness. Therefore, based on existing technology, this invention provides a device and method for simultaneous enhancement of laser-coupled plasma electropolishing under total internal reflection conditions. Summary of the Invention
[0006] To address the practical needs of simultaneous polishing and strengthening of material surfaces and the shortcomings of liquid-guided laser composite jet electrochemical processing devices, this invention proposes a device and method for simultaneous plasma electrolytic polishing and plasma electrolytic oxidation based on total internal reflection irradiation of light.
[0007] The key technical point of this invention lies in the fact that the laser beam undergoes total internal reflection on the inner wall of the tubular electrode, enabling low-loss synchronous irradiation of the plasma electrolytic processing reaction area. In the device, a superhydrophobic film is prepared on the inner wall surface of the tubular electrode through chemical treatment. Utilizing its hydrophobic properties, an optically dense medium (air film) is formed between the inner wall and the electrolyte, thereby achieving total internal reflection transmission of the laser in the optically dense medium (electrolyte). A one-way airflow valve is installed at the upper part of the tubular electrode to maintain the continuity of the air film. Part of the superhydrophobic film is removed at the lower end of the tubular electrode to maintain the stability of the air film and allow the current between the anode and cathode to flow from the area without the superhydrophobic film to the plasma electrolytic reaction area. Simultaneously, by controlling the formation of the dielectric barrier layer and the plasma discharge type during the plasma electrolytic reaction through laser energy distribution, a controllable transition between plasma electrolytic polishing and plasma electrolytic oxidation is achieved, i.e., the preparation of a surface-strengthening coating is completed simultaneously in the polishing micro-area.
[0008] The technical solution of the present invention is as follows:
[0009] A laser-plasma electrolytic polishing synchronous strengthening device based on total internal reflection conditions includes: a power supply, a laser, optical lenses, a laser beam-electrolyte coupling head, and an anode substrate;
[0010] The laser, optical lenses, and laser beam-electrolyte coupling head are located on the same central axis;
[0011] The laser beam-electrolyte coupling head consists of an upper electrolyte reservoir and a lower tubular cathode, with the two parts connected. An optical lens is embedded in the upper end of the electrolyte reservoir to allow the laser beam to pass through the electrolyte, and electrolyte inlets are provided on the left and right sides respectively. A superhydrophobic film is formed on the inner wall of the tubular cathode, and a portion (preferably 2-5 mm) of the superhydrophobic film is removed from the lower end of the tubular cathode. A one-way air inlet valve is provided at the upper end of the tubular cathode to allow air to flow unidirectionally from the outside to the inside. Preferably, the one-way air inlet valve is located 5-8 mm above the position where the laser beam first irradiates the inner wall of the tubular cathode.
[0012] The negative terminal of the power supply is connected to the outer wall of the tubular cathode of the laser beam-electrolyte coupling head, and the positive terminal of the power supply is connected to the anode substrate; the distance between the tubular cathode and the anode substrate is 5-15mm.
[0013] The laser beam energy generated by the laser is non-uniformly distributed, and the controllable variation of laser energy density at the exit of the tubular cathode is within the range of 5-25 W·mm. -2 ;
[0014] The preferred material for the laser beam-electrolyte coupling head is 316 stainless steel; the preferred tubular cathode has an outer diameter of 6-12 mm and a wall thickness of 1-2 mm.
[0015] The superhydrophobic film layer on the inner wall of the tubular cathode is formed by electrochemical etching. The specific preparation method is as follows: using 5-15 g·L -1 NaCl is used as the solute, an equal volume mixture of glycerol and water is used as the solvent, the tubular electrode of the laser beam-electrolyte coupling head is used as the anode, and a graphite strip is placed in the center of the tubular electrode of the laser beam-electrolyte coupling head as the cathode. The mixture is treated at a constant DC voltage of 15-30V for 3-12 minutes to form a micro-nano structure, which makes it superhydrophobic.
[0016] A method for simultaneous enhancement of laser-composite plasma electrolytic polishing based on total internal reflection conditions using the device of the present invention is as follows:
[0017] The plasma electropolishing-oxidation composite electrolyte is input from the electrolyte inlet of the laser beam-electrolyte coupling head. The distance between the tubular cathode and the anode substrate is adjusted to 5-15mm. A constant voltage mode voltage is provided by the power supply. While the electrical parameters are input, a non-uniform laser beam is simultaneously irradiated to form high and low laser irradiation energy zones. By gradually moving the anode substrate towards the low laser irradiation energy zone, the laser composite plasma electropolishing of the anode substrate surface is simultaneously strengthened.
[0018] in,
[0019] The composition of the plasma electropolishing-oxidation composite electrolyte is 5-15 g·L. -1 Na2HPO4, 3-12 g·L -1 NaCl, 2-10 g·L -1 NH4Cl, solvent ethylene glycol;
[0020] The electrical parameters are in constant voltage mode, with a positive voltage of 500-800V, a negative voltage of 150-300V, a pulse frequency of 2000-3000HZ, and a duty cycle of 50-80%.
[0021] Non-uniform laser irradiation refers to the simultaneous execution of plasma electropolishing and plasma electrooxidation on the anode substrate surface through laser energy distribution design, with a jump change in laser irradiation energy at the critical transition point between plasma electropolishing and plasma electrooxidation; the laser irradiation energy density in the plasma electropolishing zone is 18-25 W·mm². -2 The laser irradiation energy density in the plasma electrolytic oxidation zone is 5-10 W·mm². -2 ;
[0022] The anode substrate gradually moves towards the low laser irradiation energy region at a speed of 5-15 mm / min. -1This allows the processed micro-area to directly transform into a plasma electrolytic oxidation reaction after plasma electrolytic polishing, thereby completing the simultaneous strengthening treatment of the anode substrate surface by laser composite plasma electrolytic polishing.
[0023] The anode substrate can be additively manufactured titanium alloy, high-temperature alloy, or other parts.
[0024] The working principle of this invention includes:
[0025] A superhydrophobic coating is prepared on the inner wall of a tubular cathode. Utilizing this coating, an air film is formed between the inner wall of the tube and the electrolyte. Air is supplied through a one-way air inlet valve at the upper end of the tubular cathode to maintain the continuity of the air film. The superhydrophobic coating is removed from the lower end of the tubular cathode to seal the air film and maintain its stability. The critical angle between the water and air interface is 48.8°. The presence of the air film between the inner wall of the tube and the electrolyte provides total internal reflection conditions for laser beams with a divergence angle less than 82.4°.
[0026] By designing the laser energy distribution, the formation of the gas-solid dielectric barrier layer and the type of plasma discharge can be controlled in the polishing-oxidation composite electrolyte. Specifically, high laser irradiation energy promotes the formation of the gas film barrier layer on the anode surface, increasing its impedance and allowing more voltage to be applied to its breakdown, resulting in gas plasma discharge. Conversely, low laser irradiation energy promotes the growth of the oxide layer on the anode surface, increasing its impedance and allowing more voltage to be applied to its breakdown, resulting in solid-state plasma discharge. Furthermore, by utilizing different plasma discharge physicochemical effects, the plasma electrolysis mode can be switched, thus enabling simultaneous polishing and strengthening treatment on the anode surface.
[0027] The present invention has the following beneficial effects and advantages:
[0028] 1. Laser transmission within the tubular cathode via total internal reflection results in lower energy loss compared to traditional specular reflection. Furthermore, the optically sensitive medium for total internal reflection is the superhydrophobic coating and the air film in the electrode solution; the laser does not directly interact with the superhydrophobic coating, thus ensuring a longer lifespan.
[0029] 2. The formation process of the dielectric barrier layer on the anode surface and the plasma discharge type can be controlled by adjusting the laser energy distribution, thereby achieving a controllable transition between plasma electrolytic polishing and plasma electrolytic oxidation in the processing micro-area, and thus enabling simultaneous polishing and strengthening of the anode surface.
[0030] 3. Laser irradiation can accelerate the electrode reaction and discharge channel formation in plasma electropolishing and plasma electrooxidation, induce the electric field to significantly reduce the critical voltage of plasma electrolysis reaction, and enhance the original electric field to induce plasma, thereby improving the efficiency and quality of surface treatment.
[0031] 4. It can handle large-sized components and perform localized treatment according to the needs of different areas. Attached Figure Description
[0032] Figure 1 : A diagram of a liquid-guided laser device based on total internal reflection.
[0033] Figure 2 Schematic diagram of the laser-plasma-electrolytic polishing simultaneous strengthening method. Detailed Implementation
[0034] The present invention will be further described below with reference to the accompanying drawings and specific embodiments, but the scope of protection of the present invention is not limited thereto.
[0035] Example 1
[0036] like Figure 1 As shown, a laser-plasma electrolytic polishing synchronous enhancement device based on total internal reflection includes: a power supply 7, a 455 nm blue laser 3, an optical lens 4, a laser beam-electrolyte coupling head 5 (with a tubular electrode having an outer diameter of 8 mm and a wall thickness of 1.5 mm), a one-way air inlet valve 6, a superhydrophobic film layer 9, and an additively manufactured TC4 alloy component (anode) 10; the laser 3, optical lens 4, laser beam 2, and laser beam-electrolyte coupling head 5 are located on the same central axis; the superhydrophobic coating 9 is located on the inner wall of the tubular cathode of the laser beam-electrolyte coupling head 5, and the superhydrophobic coating 9 is applied to the inner wall of the tubular cathode of the laser beam-electrolyte coupling head 5. The lower end of the hydrophobic film layer 9 is removed by 2mm, as shown in Figure 11 after magnification; the one-way air inlet valve 6 allows air to flow unidirectionally from the outside to the inside; the one-way air inlet valve 6 is installed on the upper end of the tubular electrode of the laser beam-electrolyte coupling head 5, and is located 5mm above the position of the inner wall of the tubular electrode when the laser beam 2 first irradiates it, as shown in Figure 8 after magnification; the negative terminal of the power supply 7 is connected to the outer wall of the tubular cathode of the laser beam-electrolyte coupling head 5, and the positive terminal of the power supply 7 is connected to the anode substrate 10; the laser beam-electrolyte coupling head 5 has two opposing electrolyte inlets 1; the superhydrophobic film layer 9 on the inner wall of the tubular cathode is prepared at 10 g·L⁻¹. -1 NaCl was used as the solute, an equal volume mixture of glycerol and water was used as the solvent, the tubular cathode of the laser beam-electrolyte coupling head 5 was used as the anode, and a graphite strip was placed in the center of the tubular electrode of the laser beam-electrolyte coupling head as the cathode. The mixture was treated for 5 minutes under a constant DC voltage of 15V to form a micro-nano structure, which made it superhydrophobic.
[0037] A method for simultaneous enhancement of laser-plasma-electrolytic polishing under total internal reflection conditions, such as... Figure 2 As shown, it mainly includes the following steps.
[0038] Step 1: Use plasma electrolytic polishing-oxidation composite electrolyte 13, the solute of which is 10 g·L -1Na2HPO4, 8 g·L -1 NaCl and 10 g·L -1 The electrolyte is composed of NH4Cl and the solvent is ethylene glycol. The composite electrolyte is input from the two electrolyte inlets 1 of the laser beam-electrolyte coupling head 5, and the distance between the tubular cathode and the anode substrate 10 is adjusted to 8 mm.
[0039] Step 2: Provide constant voltage mode voltage through power supply 7, with a positive voltage of 650V, a negative voltage of 150V, a pulse frequency of 3000HZ, and a duty cycle of 70%.
[0040] Step 3: Simultaneously with the input of electrical parameters, a non-uniform laser beam 12 is synchronously irradiated. Through laser energy distribution design, plasma electropolishing 16 and plasma electrooxidation 14 on the anode surface are performed simultaneously. The laser irradiation energy at the critical transition position 15 between plasma electropolishing and plasma electrooxidation is set to change abruptly. Specifically, the laser irradiation energy density in the left plasma electropolishing area is 25 W·mm². -2 The laser irradiation energy density in the plasma electrolytic oxidation zone on the right is 5 W·mm². -2 .
[0041] Step 4: During plasma electrolytic processing, the anode substrate 10 is gradually moved towards the low laser irradiation energy range at a speed of 5 mm / min. -1 This allows the processed micro-area to directly transform into a plasma electrolytic oxidation reaction after plasma electrolytic polishing, thereby completing the synchronous strengthening treatment of the anode surface polishing, and finally forming a polishing synchronous strengthening coating with a surface roughness of less than 0.3μm and an oxide layer thickness of more than 15μm on the anode surface.
Claims
1. A method for simultaneous strengthening of laser-plasma-electrolytic polishing under total internal reflection conditions, characterized in that, The method is performed using the following apparatus: The device includes: a power supply, a laser, optical lenses, a laser beam-electrolyte coupling head, and an anode substrate; The laser, optical lenses, and laser beam-electrolyte coupling head are located on the same central axis; The laser beam-electrolyte coupling head consists of an upper electrolyte reservoir and a lower tubular electrode, with the two parts connected. An optical lens is embedded in the upper end of the electrolyte reservoir to allow the laser beam to pass through the electrolyte, and electrolyte inlets are provided on the left and right sides respectively. A superhydrophobic film is formed on the inner wall of the tubular electrode, and part of the superhydrophobic film is removed at the lower end of the tubular electrode. A one-way air inlet valve is provided at the upper end of the tubular electrode to allow air to flow unidirectionally from the outside to the inside. The negative terminal of the power supply is connected to the outer wall of the tubular electrode of the laser beam-electrolyte coupling head, and the positive terminal of the power supply is connected to the anode substrate; The method is as follows: The plasma electropolishing-oxidation composite electrolyte is input from the electrolyte inlet of the laser beam-electrolyte coupling head. The distance between the tubular electrode and the anode substrate is adjusted to 5-15 mm. A constant voltage mode voltage is provided by the power supply. While the electrical parameters are input, a non-uniform laser beam is simultaneously irradiated to form high and low laser irradiation energy zones. By gradually moving the anode substrate towards the low laser irradiation energy zone, the laser composite plasma electropolishing of the anode substrate surface is simultaneously strengthened. in, The composition of the plasma electrolytic polishing-oxidation composite electrolyte is 5-15 g·L. -1 Na2HPO4, 3-12 g·L -1 NaCl, 2-10 g·L -1 NH4Cl, solvent ethylene glycol; The electrical parameters are in constant voltage mode: positive voltage 500-800 V, negative voltage 150-300 V, pulse frequency 2000-3000 Hz, and duty cycle 50-80%. Non-uniform laser beam irradiation refers to the simultaneous execution of plasma electropolishing and plasma electrooxidation on the anode substrate surface through laser energy distribution design, with a jump change in laser irradiation energy at the critical transition point between plasma electropolishing and plasma electrooxidation; the laser irradiation energy density in the plasma electropolishing zone is 18-25 W·mm². -2 The laser irradiation energy density in the plasma electrolytic oxidation zone is 5-10 W·mm². -2 ; The anode substrate gradually moves towards the low laser irradiation energy region at a speed of 5-15 mm / min. -1 This allows the processed micro-area to directly transform into a plasma electrolytic oxidation reaction after plasma electrolytic polishing, thereby completing the simultaneous strengthening treatment of the anode substrate surface by laser composite plasma electrolytic polishing.
2. The method as described in claim 1, characterized in that, Remove a 2-5 mm superhydrophobic film layer from the lower end of the tubular electrode.
3. The method as described in claim 1, characterized in that, The one-way air inlet valve is located 5-8 mm above the position where the laser beam first irradiates the inner wall of the tubular electrode.
4. The method as described in claim 1, characterized in that, The laser beam-electrolyte coupling head is made of 316 stainless steel.
5. The method as described in claim 1, characterized in that, The tubular electrode has an outer diameter of 6-12 mm and a wall thickness of 1-2 mm.
6. The method as described in claim 1, characterized in that, The superhydrophobic film on the inner wall of the tubular electrode is formed by electrochemical etching, and the preparation method is as follows: using 5-15 g·L -1 NaCl is used as the solute, an equal volume mixture of glycerol and water is used as the solvent, the tubular electrode of the laser beam-electrolyte coupling head is used as the anode, and a graphite strip is placed in the center of the tubular electrode of the laser beam-electrolyte coupling head as the cathode. The mixture is treated at a constant DC voltage of 15-30V for 3-12 minutes to form a micro-nano structure, which makes it superhydrophobic.
7. The method as described in claim 1, characterized in that, The anode substrate is an additively manufactured titanium alloy or high-temperature alloy part.
Citation Information
Patent Citations
Laser microjet processing device for perforating turbine blade
CN105195903A
Optical fiber laser and electrolysis coaxial and synchronous combined machining device
CN113579380A